Mainstreaming in Higher Education: an integrating review (Research, Society and Development, 2020)
This research analyzed the scientific production on the mainstreaming of students with disabilities in higher education in health area. For this, an integrative literature review were collected between December 2018 and January 2019 in databases: Nursing Database – BDENF, Latin American and Caribbean Literature in Health Sciences – LILACS, International Literature in Health Sciences – MEDLINE, Dentistry – BBO, Index Psicologia and Index Psicologia – Theses, included in the Virtual Health Library (BVS) and in the National Library of Medicine National Institutes of Health of the USA – PubMed through the descriptors registered in "Health Sciences Descriptors”: “mainstreaming”, “education, higher” and “disabled persons”. Twelve articles were identified and analyzed, which evidenced the categories: Process of inclusion of students with disabilities in Higher Education; Mapping the enrollment of students with disabilities; Sectors responsible for accessibility; Teacher’s experiences on inclusion of disabled persons; Creation of dental signs language. The analysis evidenced weaknesses, such as difficulties in the inclusion process, flaws in the student mapping process and lack of teacher training, but also strengths such as changes in architectural barriers and exclusive sectors responsible for process that is still a challenge in the Brazilian reality and still has a long and arduous road ahead, requiring more studies to support the debates and reflections on the subject.